2023
DOI: 10.1101/2023.11.19.567585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral expansion after transfer is a primary driver of influenza A virus transmission bottlenecks

Katie E. Holmes,
David VanInsberghe,
Lucas M. Ferreri
et al.

Abstract: For many viruses, narrow bottlenecks acting during transmission sharply reduce genetic diversity in a recipient host relative to the donor. Since genetic diversity represents adaptive potential, such losses of diversity are though to limit the opportunity for viral populations to undergo antigenic change and other adaptive processes. Thus, a detailed picture of evolutionary dynamics during transmission is critical to understanding the forces driving viral evolution at an epidemiologic scale. To advance this un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Virus transmission can be conceptualized as a series of bottlenecks, including but not limited to transfer to a new host and expansion within that host. A recent study by Holmes et al 22 using BC influenza reported much higher BC counts in contact animals 1-2 days post-exposure than at later timepoints, demonstrating that expansion is a major bottleneck in influenza transmission. To assess whether expansion also imposes a bottleneck on SARS-CoV-2 transmission, we collected the respiratory tissues from airborne-exposed contact hamsters 24 and 48hpe ( Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Virus transmission can be conceptualized as a series of bottlenecks, including but not limited to transfer to a new host and expansion within that host. A recent study by Holmes et al 22 using BC influenza reported much higher BC counts in contact animals 1-2 days post-exposure than at later timepoints, demonstrating that expansion is a major bottleneck in influenza transmission. To assess whether expansion also imposes a bottleneck on SARS-CoV-2 transmission, we collected the respiratory tissues from airborne-exposed contact hamsters 24 and 48hpe ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…These findings also highlight differences between SARS-CoV-2 and other respiratory viruses. As mentioned above, in influenza transmission, expansion in contacts is a stringent bottleneck 22 . We detected no evidence of a bottleneck during expansion in SARS-CoV-2 ( Fig S3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation